Response of mussel population to sewage-impact in rocky-stony shore - Vallarino, Eduardo Alberto (2014)
In Mar del Plata, a rocky-stony-shore near a sewage discharge develops a community of Brachidontes rodriguezii. Samples along a gradient of organic contamination and a control site were selected randomly for studies of density, proportion of adults/seeds, biomass, and length, width and height of mussels. Density of adults, seeds and biomass were significantly lowest nearest to outfall increasing to control sites. In spite of the high mortality of seeds, the surviving mussel seems to have better condition near the sewage outfall. Unexpected allometric results showed greatest values of length, width and height near the outfall rather than in control site. After summer, Biomass and size of mussel were lower as results of increasing sewage discharge.